Techno-historical limits of the interface: the performance of interactive narrative experiences - Hutchison, Andrew (Curtin University, 2009)
This thesis takes the position that current analyses of digitally mediated interactive experiences that include narrative elements often lack adequate consideration of the technical and historical contexts of their production.From this position, this thesis asks the question: how is the reader/player/user's participation in interactive narrative experiences (such as hypertext fiction, interactive fiction, computer games, and electronic art) influenced by the technical and historical limitations of the interface?In order to investigate this question, this thesis develops a single methodology from relevant media and narrative theory, in order to facilitate a comparative analysis of well known exemplars from distinct categories of digitally mediated experiences. These exemplars are the interactive fiction Adventure, the interactive art work Osmose, the hypertext fiction Afternoon, a story, and the computer/video games Myst, Doom, Half Life and Everquest.The main argument of this thesis is that the technical limits of new media experiences cause significant ‘gaps’ in the reader’s experience of them, and that the cause of these gaps is the lack of a dedicated technology for new media, which instead ‘borrows’ technology from other fields. These gaps are overcome by a greater dependence upon the reader’s cognitive abilities than other media forms. This greater dependence can be described as a ‘performance’ by the reader/player/user, utilising Eco’s definition of an ‘open’ work (Eco 21).This thesis further argues that the ‘mimetic’ and ‘immersive’ ambitions of current new media practice can increases these gaps, rather than overcoming them. The thesis also presents the case that these ‘gaps’ are often not caused by technical limits in the present, but are oversights by the author/designers that have arisen as the product of a craft culture that has been subject to significant technical limitations in the past. Compromises that originally existed to overcome technical limits have become conventions of the reader/player/user’s interactive literacy, even though these conventions impinge on the experience, and are no longer necessary because of subsequent technical advances. As a result, current new media users and designers now think of these limitations as natural.This thesis concludes the argument by redefining ‘immersion’ as the investment the reader makes to overcome the gaps in an experience, and suggests that this investment is an important aspect of their performance of the work.